Four new combinations in Phanera (Leguminosae: Cercidoideae) from some countries of Indo-China - Bandyopadhyay, Subir; Kumar, Anand (Phytotaxa, 2024)
In the course of preparing a list of Bauhinia Linnaeus (1753: 374) and allied genera for the Legume Taxonomy Working Group, we found that new combinations are needed in Phanera Loureiro (1790: 37) for four species of Bauhinia endemic to some countries of Indo-China following the recent circumscription of the genus Phanera (Lewis & Forest 2005, Bruneau et al. 2008, Sinou et al. 2009, LPWG 2017, Clark et al. 2017, Sinou et al. 2020).